Produção de farinha da entrecasca de melancia destinada a formulações de biscoitos - Lima, Jacinete Pereira (2013)
The flour obtained from the watermelon bast is a byproduct with important nutritional characteristics, which is being considered a promising alternative for the development of new products. The objectives of this work were to study the process of the production of the flour from the white part of watermelon and the development of new cookies source and rich in dietary fiber. The flour was obtained by convective drying using the following conditions: temperature of 60°C, process duration of 240 minutes and air velocity of 3.0 m/s, followed by milling, grinding and sieving processes. The physico-chemical compositions were determined for the raw material, the flour and the cookies. The cookies formulations used were three: control (CT), source of dietary fiber (F1) and rich in dietary fiber (F2). For the sensory evaluation, forty-eight untrained panelists received samples of these biscuits and performed the sensory tests of acceptability, using a 9 point hedonic scale. Data analysis was performed using analysis of variance (ANOVA), using the statistical software Assistat 7.4 beta. For the flour, it was found values of moisture (9.55%) and ash (9.97%) contents within the current legislation standards, and high value of dietary fiber (33.30%) and minerals. The cookies formulated presented lower moisture content, water activity and protein, and higher contents of carbohydrates and ash. Regarding the analysis of acceptability, formulations F1 and CT obtained scores ≥ 6, with the attributes of color and texture as the most relevant. The flour from the white part of watermelon can be considered a great alternative as an ingredient in baked goods.